Polar Stratospheric Cloud Simulations for CRISTA-NF ... - Kalicinsky, Christoph; Grießbach, Sabine; Spang, Reinhold (Jülich DATA, 2020)
This data set contains simulated infrared limb emission spectra in the presence of polar stratospheric clouds (PSCs) for the air-borne CRyogenic Infrared Spectrometers and Telescopes for the Atmosphere - New Frontiers (CRISTA-NF). The atmospheric background conditions for the simulations represent the Arctic winter 2009/2010, in which PSCs were measured during the RECONCILE campaign. While the PSCs of 0.5, 1, 2, 4, and 8 km thickness are located between 13 and 30 km altitude, the spectra are available for altitudes between 10 km and the flight altitude of 18.4 km with 100 m vertical spacing. Two spectral ranges, from 785 to 840 cm-1 and 940 to 965 cm-1 are provided. The simulated PSC scenarios comprise pure ice, NAT, and STS scenarios, described by mono-modal log-normal particle size distributions, and two mixed scenarios STS/NAT and small NAT/large NAT, both described by bi-modal log-normal particle size distributions. For STS PSCs we followed the setup in Spang et al. (2012) and simulated three mixtures ...